PRODUCTIVE LONGEVITY AND REPRODUCTIVE QUALITY OF HOLSTEIN COWS OF FOREIGN BREEDING - V. G. Semenov; D. A. Baimukanov; A. S. Alentayev; R. M. Mudarisov; S. G. Kondruchina; A. K. Karynbayev (Scientific Journal of Pedagogy and Economics, 2021)
The aim of this work is to determine the productive longevity of Holstein cows of different breedings. The results of the research showed that Finnish animals were superior in life expectancy and productive longevity, exceeding German breeding cows by 74 days (P<0.05) and Hungarian cows by 24 days, and by 0.06 and 0.12 lactations in the productive period respectively. At the same time, according to the level of average productivity per lactation and lifelong milk yield, the highest rates were established for the group of Hungarian cows. So, their average milk yield per lactation was higher: compared to other groups by 529.2 kg and 561.8 kg or 7.6 % and 8.1%; lifelong milk yield by 1305.5 kg and 996 kg (5.6 % and 4.2%); per one day of calving interval - by 0.64 kg and 0.8 kg (3.6 % and 4.6%) and per one day of life - by 0.56 kg and 0.60 kg or by 3.2 % and 5.6%. In the context of the group of cows of the German and Finnish breeding, no significant differences were noted by these indicators. The duration of pregnancy in experimental cows ranged from 285-289 days. The analysis of the obtained data indicates that the cellular protection indicators of Holstein cows are within the physiological norm. So, phagocytic activity, which expresses the percentage of active leukocytes participating in phagocytosis to the total number of counted neutrophilic leukocytes, is higher in animals of the German breeding compared with Hungarian animals - by 13.2% and with Finnish ones - by 13.4%. The phagocytic index is defined by the average number of phagocytosed microorganisms per active leukocyte and characterizes the intensity of phagocytosis. In our experiment, the intensity of phagocytosis was higher in the German cows and amounted to 8.42, which exceeds this indicator by 11.4% compared with animals of the Hungarian breeding and by 3.3% compared to the Finnish animals.